A high-durability palladium catalyst for the oxygen reduction reaction in an alkaline environment - Bae, Hyo Eun; Park, Ji Eun; Huynh, T. B. Ngoc; Song, Jihyeok; Cho, Sung Ki; Sung, Yung-Eun; Cho, Yong-Hun; Kwon, Oh Joong (Royal Society of Chemistry, 2024)
The Pd@CS/CNF800 catalyst, encapsulated in an N-doped carbon shell, was synthesized through a redox reaction between aniline and a metal precursor, followed by formation of a carbon shell via heat treatment. The structure, comprising less than two layers of a porous carbon shell, effectively facilitates oxygen transport, resulting in rapid 4-electron reactivity while maintaining structural integrity even after durability tests due to the protective carbon shell. Compared to commercial catalysts, the mass activity (MA) was improved by more than 2.2-fold, with only a 4 mV decrease in half-wave potential after accelerated stress tests (ASTs), retaining over 80% of its initial MA. Furthermore, when applied in an anion exchange membrane fuel cell (AEMFC), it showed an enhanced current density of 504 mA cm-2 at 0.6 V which was 2 times higher than that of commercial catalysts, confirming its outstanding activity. This was further demonstrated by achieving a specific power density of 2.4 W mgtotal-1.